2019
DOI: 10.1038/s41598-019-54022-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical studies on the distribution of arabinogalactan proteins (AGPs) as a response to fungal infection in Malus x domestica fruit

Abstract: Arabinogalactan proteins (AGPs) are cell components implicated in plant-microbe interactions. Despite the significance of AGPs in response to stress factors, their distribution during development of fungal disease in fruit is unknown. In our work, in situ analysis of AGP arrangement in fruit inoculated with Penicillium spinulosum during the consecutive days of infection development was carried out. For immunolocalization of AGPs, samples were incubated with JIM13, MAC207, LM2, and LM14 antibodies recognizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Furthermore, the localisation of AGPs was found to depend on the condition of the cell wall–plasma membrane changing during the postharvest storage as a result of senescence process. Various investigations primarily show changes in the aforementioned pattern as a presumed mechanism of plant adaptation in response to environmental stress factors, such as fungal infection [ 43 , 44 , 45 ]. Moreover, super-resolution imaging with Stimulated Emission Depletion Microscopy (STED), combined with immunocytochemical analyses used to visualise the dynamic behaviour of AGPs, has also shown that AGPs are extracellular cargo receptors and migrate across the plasma membrane to initiate endocytosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the localisation of AGPs was found to depend on the condition of the cell wall–plasma membrane changing during the postharvest storage as a result of senescence process. Various investigations primarily show changes in the aforementioned pattern as a presumed mechanism of plant adaptation in response to environmental stress factors, such as fungal infection [ 43 , 44 , 45 ]. Moreover, super-resolution imaging with Stimulated Emission Depletion Microscopy (STED), combined with immunocytochemical analyses used to visualise the dynamic behaviour of AGPs, has also shown that AGPs are extracellular cargo receptors and migrate across the plasma membrane to initiate endocytosis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since today AGPs were examined in a few kinds of fruit, such as goji berry— Lycium chinese 11 , Lycium ruthenicum 47 , tomato— Salanum lycopersicum 24 , grape— Vitis vinifera 48 , apple— Malus domestica 49 52 , and pear — Pyrus communis 53 . Generally, in all these studies, AGPs are characterized as cell wall elements, which are closely related to other polysaccharide constituents with a strong emphasis on their involvement in fruit ripening indicating that particular attention was given mainly on the structural and not the functional features of AGPs.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the frequency of occurrence of AGP’s hydroxylation and possibly glycosylation by either silencing or overexpressing prolyl 4 hydroxylases might alter their structure and subsequently their function leading to changes in fruit growth and ripening. Previously, the silencing of three tomato P4Hs, SlP4H1, SlP4H7, and SlP4H9 by Virus-Induced Gene Silencing (VIGS) resulted in the reduction on the JIM8 AGPs-bound and JIM11 extensin-bound epitopes which might be attributed either to lower levels of AGPs and extensins or to alterations in their glycan structure affecting the binding of the antibodies 52 . Genetic analysis of knock out mutants of Arabidopsis hydroxyproline-galactosyltransferases (Hyp-GALT), which add arabinogalactan polysaccharides in AGPs, showed pleiotropic growth and development phenotypes which were attributed to reduced activity of Hyp-GALT indicating that the AGP glycans are essential for the function of AGPs 22 , 56 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations